The Impact of Doses of Compost ofCow Manure on Soil Temperature Profiles in the Root Zone and Productivity of Brassica rafa - Wijaya, I Made Andi Purnama; Setiyo, Yohanes; Tika, I Wayan (Jurnal BETA (Biosistem dan Teknik Pertanian), 2019)
The temperature of the soil is one of the physical properties of the soil, this soil physical properties direc2tlyaffect plant growth pakcoy. The purpose of this research are (1) to analyze the temperature at root zone, temperature inside and out of the mini greenhouse, (2) analyze the relationship between temperature at root zone with doses of compost fertilizer application and (3) to analyze the optimum dose of compost based on productivity and quality of the pakcoy is generated when the harvest. The design of the research used randomized complete design, with five treatments and three replicates. The treatment is P0: a dose of compost 0 kg/m, P1: a dose of compost 1 kg/m2, P2: a dose of compost 2 kg/m2, P3: the dose of compost 3kg/m2, and P4: a dose of compost 4 kg/m2. The parameters observed in this research is the air temperature, the temperature of the environment, ground water levels and productivity. At night the temperature of the soil rooting zone higher at 0.59 ºC than at the temperature of the environment. Soil temperature at root zone the lowest and the highest are 18.02 oC and 21.94 oC. The temperature of the soil the night and during the day for dose 0-5 kg/m2 was still tolerant plants pakcoy. Dry weight of the plant the highest pakcoy on the treatment dose of compost 4 kg/m2 with a weight of 92.21 grams/lowest at the treatment plant and the control by the weight of 71.82 grams/plant.